LONG-TERM SUBSIDENCE OF A MULTISTORY BUILDING ON THE BASE REINFORCED WITH SOIL CEMENT ELEMENTS - Vynnykov, Yu. L.; Miroshnychenko, I. V.; Landar, О. М.; Zotsenko, V. М.; Omelchenko, P. M. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The methodology and results of long-term geodetic observation at subsidence of nine-ten storey building with a strip cast-in-place foundation on sandy and peaty base reinforced with soil cement elements at the process of its construction and exploitation are presented in the article. The correctness of elastic-plastic model use with Mohr Coulomb strength criterion and planar task finite element method for the evaluation of the deformed state «strip foundation – reinforced soil layer – the natural basis» system are substantiated.